2012
DOI: 10.1007/s10142-011-0260-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel mechanism of conjoined gene formation in the human genome

Abstract: Recently, conjoined genes (CGs) have emerged as important genetic factors necessary for understanding the human genome. However, their formation mechanism and precise structures have remained mysterious. Based on a detailed structural analysis of 57 human CG transcript variants (CGTVs, discovered in this study) and all (833) known CGs in the human genome, we discovered that the poly(A) signal site from the upstream parent gene region is completely removed via the skipping or truncation of the final exon; conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 17 publications
3
31
1
Order By: Relevance
“…As the biological and clinical significance of such events are still unknown, the detection of EML4/ALK fusion transcripts without confirmation by FISH or IHC cannot be considered positive. 34 In summary, our data strongly support the necessity of combining all current diagnostic approaches for optimal ALK testing in NSCLC. Immunohistochemistry seems to be the most reliable screening method for large-scale clinical practice, when performed with a sensitive antibody clone and enhanced amplification system.…”
Section: Commentsupporting
confidence: 65%
“…As the biological and clinical significance of such events are still unknown, the detection of EML4/ALK fusion transcripts without confirmation by FISH or IHC cannot be considered positive. 34 In summary, our data strongly support the necessity of combining all current diagnostic approaches for optimal ALK testing in NSCLC. Immunohistochemistry seems to be the most reliable screening method for large-scale clinical practice, when performed with a sensitive antibody clone and enhanced amplification system.…”
Section: Commentsupporting
confidence: 65%
“…In fact, transcription-induced chimeric RNAs, generated in normal healthy cells, without corresponding genomic rearrangements have been well recognized in the field of genetic research (Akiva, 2005;Fang et al, 2012;Gingeras, 2009;Kim DS, et al, 2007;Kim DS, et al, 2012;Kim P, et al, 2010;Kim RN, et al, 2012;Li et al, 2008;Parra, 2005;Prakash et al, 2010;Thomson et al, 2000;Zhang et al, 2012). However, the existence of transcription-induced chimeric RNAs has not been well appreciated in the cancer research field, where fusion genes play an important role in disease development, progression, and treatment (Edwards, 2010;Mitelman et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of formation and the functional roles of chimeric transcripts remain elusive (Kannan et al, 2011;Kim RN, et al, 2012;Parra, 2005), two main mechanisms involved in the generation of transcription-induced chimeric transcripts have been established: 1) Through conjoined genes (two or more closely located genes on the same strand of a chromosome (Kannan et al, 2011;Kim DS, et al, 2012;Kim RN, et al, 2012;Parra, 2005;Prakash et al, 2010), where chimeric transcripts can be generated either by run-off transcription of the upstream gene followed by cis-splicing (Kannan et al, 2011;Prakash et al, 2010;Zhang et al, 2012) or skipping/truncation of the final exon in the upstream gene (Kim RN, et al, 2012); 2) Trans-splicing of RNAs, which generates inter-and intra-chromosomal chimeric transcripts (Fang et al, 2012;Gingeras, 2009;Kannan et al, 2011;Li et al, 2008). The USP9Y and TTTY15 genes are located next to each other in the same direction, meeting the criteria for a conjoined gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3), in line with Wernersson et al (29) who found INS-IGF2 expression to be barely detectable in normal pancreatic tissue. kim et al (35) states that read-through transcripts are expressed at extremely low levels in human tissues with read-through transcripts showing a tumor-biased expression. Increased expression-level of read-through transcripts and increased number of read-through transcripts expressed seems therefore to be a cancer-specific event (35).…”
Section: Discussionmentioning
confidence: 99%